Sub-100 Femtosecond All-Optical Modulation Beyond Electron–Phonon Limits - Gao, Renxian; Li, Jiayu; Dong, Xiaoxiang; He, Yonglin; Chen, Wenbin; Ren, Peiwen; Zhao, Xiaoyu; Li, Ming‑De; Yang, Zhilin (Nano-Micro Letters, 2026)
Ultrafast all-optical modulators are central to the advancement of next-generation photonic computing and signal-processing systems. However, the intrinsic electron–phonon relaxation bottleneck in plasmonic materials has long constrained modulation speeds to the picosecond regime, hindering the realization of sub-100 fs modulation. Here, we report a metastructured silver–single-crystal silicon nanodisk antenna that delivers experimentally resolved sub-100 fs all-optical modulation. Distinct from conventional planar metal–semiconductor junctions, the nanodisk architecture spatially co-localizes plasmonic energy deposition with the metal–semiconductor transfer boundary within a nanoscale-confined volume. This configuration markedly shortens hot-carrier transport pathways and preferentially activates interfacial carrier extraction during the earliest relaxation stage, thereby establishing an interface-dominated modulation pathway that precedes electron–phonon thermalization. By enabling modulation on timescales comparable to intrinsic electronic response limits, this work establishes a physical foundation for ultrafast photonic modulation, including femtosecond free-space photonic computing architectures, temporal optical gating, and other ultrafast systems constrained by carrier or cavity lifetimes. Highlights: 1 Engineered Ag–Si interfacial plasmonic modes enable deconvolution-verified sub-100 fs all-optical modulation, overcoming the temporal bottleneck imposed by electron–phonon relaxation in conventional plasmonic structures. 2 A unified electromagnetic–thermal physical model reveals an interface-governed nonthermal carrier extraction pathway faster than electron–electron and electron–phonon scattering, quantitatively explaining the observed sub-100 fs dynamics.